(untitled) (Ius Novum, 2022)
The article discusses the statutory features of the offence of incest in the Polish Penal Code from 1997 (Article 201) and the results of empirical research carried out. Doubts were raised in doctrine about the rationalization of the prohibition of incest and the definition of the object of protection of this crime. The conduct that constitutes the actus reus as well as the subject and the subjective side of the offence of incest were also analysed. The research material was the files of cases under Article 201 of the Penal Code registered in all public prosecutor’s offices in Poland in 2013–2014 (389 cases). Research was intended to was primarily to identify the criminological picture of the offence of incest and its scale compared to total crime figures in Poland and the policy of punishing. The next aim of the research was to characterise the families, in which incestuous acts took place, and thus to answer the key questions in this context: whether incest is a factor determining the so-called family pathology or maybe it is a phenomenon conditioned by it and whether it occurs spontaneously or is connected with sexual violence in the family. The results of the research show that the so-called “regular incest” (voluntary on both sides), qualified only under Article 201 of the Polish Penal Code, is relatively rare in the practice of the judiciary. Most cases of incestuous sexual relations were combined with the crime type of sexual abuse of a minor or rape. These results seem to confirm the thesis that incest is rarely the only committed offence, but is most often related to domestic sexual violence. They also support the thesis that incest is a phenomenon conditioned by already existing family dysfunctionality, not its cause.